Conquering the world : the War Scroll (1QM) reconsidered - Schultz, Brian, 1968- (Studies on the Texts of the Desert of Judah, 2009)
Unique in its genre and content, the War Scroll (1QM) presents a vision of an impending eschatological war. Although originally interpreted as being the product of a single author from the Qumran Sect, the composition's inconsistencies quickly led to the view that it is in fact an eclectic document with an elaborate compositional history. Yet all such theories were formulated prior to the publication of War Scroll-like texts from Caves 4 and 11. A careful re-examination of the War Scroll suggests instead that what began as a primitive and cohesive composition from the Hellenistic period about a two-stage conquest of the world was eventually updated in order to fit the new historical realities faced by the sectarians under Roman rule.